Microwave-assisted solvothermal synthesis and performances of LiMn0.7Fe0.3PO4 nanoplates. Issue 8 (11th June 2018) - Guo, Zhanjun; Chen, Zhiliang
ABSTRACT: LiFe x Mn1- x PO4 ( x  = 0 ~ 1) cathode materials were widely studied in the past few years. The results show that this olivine-structured material would present higher energy density that can be achieved at higher Mn content. However, the specific capacity and rate capability of the LiFe x Mn1- x PO4 would decrease with decrease of x from results of various studies. Here, we chose the optimal x value of 0.3 and successfully synthesized the pure LiMn0.7 Fe0.3 PO4 via microwave-solvothermal method at 200°C with a short reaction time of 10 min. In spite of the low synthesis temperature, the as-synthesized powders with thinner thickness along [010] direction are highly crystalline. Sample exhibited excellent rate capability and showed good cyclic performance. The short reaction times of just 10 min show the basis for an efficient and time-saving synthesis of nanosized LiMn0.7 Fe0.3 PO4 .